2003
DOI: 10.1375/brim.4.2.91.27029
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Behaviours and Relationships Following Mild to Moderate Childhood Traumatic Brain Injury: Preliminary Findings

Abstract: Recent attention has begun to focus on the impact of childhood traumatic brain injury (TBI) on the family. This study examined the impact of mild to moderate childhood TBI on parental ratings of well and injured siblings' behaviours in relation to well siblings' ratings of the impact of injury and the sibling relationship. Parents of 10 children with TBI and 10 children with orthopaedic injury rated both injured and well siblings' behaviours using the Child Behaviour Checklist (CBCL). Well siblings completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Moreover, emotional-behavioural outcome of siblings whose brother or sister sustained Paediatric traumatic brain injury: A review of siblings' outcome moderate-to-severe TBI was found to be comparable to controls in studies conducted by McMahon et al [45] and Swift et al [46]. On the other hand, in a most recent study that included siblings of children who sustained TBI of lesser severity (mild-tomoderate rather than moderate-to-severe), Fay and Barker-Collo [47] found that these siblings exhibited significantly more (internalizing but not externalizing) behavioural difficulties than control siblings. The reasons for this discrepancy are not entirely clear.…”
Section: Sibling Response To Paediatric Tbimentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, emotional-behavioural outcome of siblings whose brother or sister sustained Paediatric traumatic brain injury: A review of siblings' outcome moderate-to-severe TBI was found to be comparable to controls in studies conducted by McMahon et al [45] and Swift et al [46]. On the other hand, in a most recent study that included siblings of children who sustained TBI of lesser severity (mild-tomoderate rather than moderate-to-severe), Fay and Barker-Collo [47] found that these siblings exhibited significantly more (internalizing but not externalizing) behavioural difficulties than control siblings. The reasons for this discrepancy are not entirely clear.…”
Section: Sibling Response To Paediatric Tbimentioning
confidence: 96%
“…Finally, none of these papers contained information on pre-accident sibling behaviour. Fay and BarkerCollo [47] argued that a high level of internalizing behavioural difficulties found in their sample was secondary to the significantly higher level of externalizing behavioural problems reported by parents in the TBI group. McMahon et al [45] did not report on the behavioural features of the TBI group.…”
Section: Sibling Response To Paediatric Tbimentioning
confidence: 96%
See 3 more Smart Citations